Identification method and application of order parameters for organizational systems considering time-series values: A case study on high-quality development in China’s regional manufacturing industry - Xin Wen; Yuqing Zhou (PLoS ONE, 2025)
The transition from disorder to order in the evolution of organizational systems is driven by the identification of key order parameters, which serve as critical determinants of this shift and the primary forces behind system evolution. Since order parameters capture the dominant state of the system at specific time points, accurately identifying these parameters is essential for tracing the evolutionary trajectory. This study integrates time-series values into the process of order parameter identification and employs the CRITIC method to objectively calculate the weights of these values, thereby enhancing the scientific rigor and effectiveness of the identification process. The results indicate that the identified order parameters accurately reflect the actual evolutionary state of the system. Furthermore, this method efficiently controls order parameters throughout the evolution of the system, providing operational and technical references for subsequent development processes. By focusing on a case study of high-quality development in the manufacturing industry in China, this study validates the practical application of the proposed method and highlights the significance of order parameter identification in enhancing organizational system development.